ARTIFICIAL INTELLIGENCE IN PROGRAMMING: HOW ШІ IS CHANGING THE APPROACH TO CODE DEVELOPMENT AND AUTOMATION - KRAVCHUK, OLHA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article discusses the impact of artificial intelligence on programming processes, including code automation, algorithm optimisation, and testing. The article analyses current research in the field of AI programming, the main challenges faced by developers, and the prospects for further development of the technology. The main attention is paid to the efficiency, security and ethics of using artificial intelligence in software development. The paper contains an analysis of relevant scientific publications and identifies possible areas for future research.Artificial intelligence has long ceased to be a science fiction concept and has become an important part of many industries, including programming. It helps to automate complex processes, optimise code, and increase developer productivity. In recent years, AI tools have become an integral part of the developer workflow, helping to write code faster, detect errors at early stages, and even create new algorithms. This not only speeds up the work but also changes the very approach to software development.Thanks to artificial intelligence technologies, programming becomes more accessible and efficient, which opens up new opportunities for both experienced developers and beginners. In this article, we will consider how artificial intelligence changes programming, what tools exist, and what challenges developers face in the world of automated development.The introduction of artificial intelligence into programming brings both significant benefits and challenges. The main problem is the balance between automation and maintaining human control. Automated code writing and optimisation can reduce development time, but at the same time raise questions of security, ethics, and trust in machine solutions.From a scientific point of view, research in AI programming is focused on improving machine learning models, reducing error rates, improving integration with modern programming languages, and developing self-learning algorithms. On the practical side, companies and developers seek to minimise the risks associated with the use of artificial intelligence, avoid code duplication, and create more efficient automated processes.Thus, the study of artificial intelligence in programming is critical for the development of modern technologies, as it allows not only to increase productivity but also to ensure the safe and ethical use of artificial intelligence in software engineering.
Keywords: artificial intelligence; programming; code automation; machine learning; testing; algorithm optimisation; ШІ ethics; cybersecurity